2008
DOI: 10.1093/rpd/ncn082
|View full text |Cite
|
Sign up to set email alerts
|

Overview of double dosimetry procedures for the determination of the effective dose to the interventional radiology staff

Abstract: In interventional radiology, for an accurate determination of effective dose to the staff, measurements with two dosemeters have been recommended, one located above and one under the protective apron. Such 'double dosimetry' practices and the algorithms used for the determination of effective dose were reviewed in this study by circulating a questionnaire and by an extensive literature search. The results indicated that regulations for double dosimetry almost do not exist and there is no firm consensus on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 14 publications
2
44
0
2
Order By: Relevance
“…Values for parameters F 2 and M 2 as found in the literature, and very recently summarized by Järvinen et al [47], are shown in Table 4.…”
Section: Algorithm For Double Dosimetrymentioning
confidence: 87%
See 2 more Smart Citations
“…Values for parameters F 2 and M 2 as found in the literature, and very recently summarized by Järvinen et al [47], are shown in Table 4.…”
Section: Algorithm For Double Dosimetrymentioning
confidence: 87%
“…In a recent multi-centre study [47] it was concluded that the difference between the accuracy of double and single dosimetry algorithms was not significant. This immediately was weakened by the limited number of exposure conditions that could be considered.…”
Section: The Number Of Dosemetersmentioning
confidence: 96%
See 1 more Smart Citation
“…Using this criterion, 87% of catheters lose their functionality at least once during their lives (5). Severe poor functionality that leads to catheter replacement occurs in 16% of catheters depending on the type of catheter (6).…”
Section: Introductionmentioning
confidence: 99%
“…Conventional effective dose estimates based on H p (10) at the position of the personal dosimeter can therefore considerably underestimate the actual effective dose to a person (Faulkner and Marshall 1993;NCRP 1995). Several authors have discussed the use of a second dosimeter placed on the anterior area of the neck to improve the estimates (Covens et al 2007;Järvinen et al 2007;Kim et al 2008;Lachmund 2005;NCRP 1995;Niklason et al 1994;Padovani et al 2001;Rosenstein and Webster 1994;Schultz and Zoetelief 2006;Sherbini and DeCicco 2002;Webster 1989). In this double dosimetry concept, one dosimeter at the classical position on the anterior chest behind the apron would represent the body area covered by the protective garment while a second dosimeter measures a typical dose for those areas which are not or not completely shielded by the apron.…”
Section: Introductionmentioning
confidence: 99%